2016
DOI: 10.4103/0019-5049.174870
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative cardiovascular investigations in liver transplant candidate: An update

Abstract: Cardiovascular complications are a major cause of morbidity and mortality in patients with end-stage liver disease (ESLD) undergoing liver transplantation. Identifying candidates at the highest risk of postoperative cardiovascular complications is the cornerstone for optimizing the outcome. Ischaemic heart disease contributes to major portion of cardiovascular complications and therefore warrants evaluation in the preoperative period. Patients of ESLD usually demonstrate increased cardiac output, compromised v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…This includes a full history and examination, 12-lead ECG, and two-dimensional echocardiography to detect structural and functional heart abnormalities and estimate pulmonary artery pressure. Basedon the findings of the initial screening test, liver transplant recipients who are at high-risk for coronary artery disease undergo further invasive investigations such as dobutamine stress echocardiography, coronary angiography, and coronary computed tomography angiography (CCTA) [80].…”
Section: Predictors and Diagnostic Approachmentioning
confidence: 99%
“…This includes a full history and examination, 12-lead ECG, and two-dimensional echocardiography to detect structural and functional heart abnormalities and estimate pulmonary artery pressure. Basedon the findings of the initial screening test, liver transplant recipients who are at high-risk for coronary artery disease undergo further invasive investigations such as dobutamine stress echocardiography, coronary angiography, and coronary computed tomography angiography (CCTA) [80].…”
Section: Predictors and Diagnostic Approachmentioning
confidence: 99%
“…The CO response to dobutamine has been suggested as a way to identify patients at higher risk of cardiovascular complications during LT. (67,75,76) A recent study modeled 3 different simulated scenarios using data from a 6-year-old child with AS undergoing catheter/dobutamine stress magnetic resonance imaging (DSMRI) and concluded that there was impaired coronary flow reserve, which was undetected by DSMRI and resulted in myocardial ischemia. (77) It is possible that by using computational data, this novel approach to risk stratification could be useful to predict morbidity and mortality after LT in children with congenital cardiac disease or CCM.…”
Section: Selection For Transplantationmentioning
confidence: 99%
“…A 6-minute walk test also has been found to have significantly lower sensitivity in ESLD patients. 19 This test has been evaluated in few studies with small patient numbers, 3 and its predictive role for posttransplant outcomes is still unclear. Coronary calcium scoring is an acceptable tool to identify early atherosclerotic disease in asymptomatic LT candidates.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular disease in ESLD patients may vary from minimal electrocardiogram (ECG) changes to heart failure. 3 The most common cardiovascular conditions in ESLD are QT interval prolongation, hypertension, ischemic heart disease, cardiomyopathies (systolic and/or diastolic dysfunction), heart failure, hepatopulmonary syndrome, and portopulmonary hypertension. 3 Corrected QT interval prolongation is the most common ECG abnormality among LT candidates (45% of cirrhotic patients).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation